On Wooden Pillows: Multiple Classification and Children's Category-Based Inductions - Kalish, Charles W.; Gelman, Susan A. (Child development, 1992)
Previous research has indicated that preschoolers do not distinguish between properties that are generalizable within a given category and those that are not. 2 possible general constraints on children's cognition are proposed to account for these findings. 3 studies are reported that argue against the presence of such general constraints. We examine preschoolers' understanding of the properties associated with material (e. g., wood, cotton) and object (e. g., chair, pillow) categories. In Study 1, subjects consistently made inductions based on the material compositions of items when asked to predict texture and fragility. In Study 2, the same subjects judged that items that shared material would share an unfamiliar dispositional property (e. g., gets sodden in water), but items that shared object kind would share a novel functional property (e. g., used for accelerating). Study 3 tested a younger sample of 3-year-olds and found the same sensitivity to category type, albeit with larger individual differences. By age 3, children use different modes of categorization to generalize different kinds of phenomena. These results argue against general limitations on children's abilities to use categories to make inductions. Even when children lack specific theoretical knowledge, the ability to organize phenomena into domains allows children to recognize which categories are relevant in different situations. This understanding can provide a basis for the development of more specific theories.